Safety and effectiveness of percutaneous renal cryoablation with conscious sedation. Issue 3 (2nd July 2020) - Patel, Sagar Rohitkumar; Francois, Sean; Bhamber, Tiagpaul; Evans, Holt; Gaston, Kris; Riggs, Stephen B.; Teigland, Chris; Clark, Peter E.; Roy, Ornob P.
ABSTRACT: Objective: To investigate complications and treatment failure rates of percutaneous renal cryoablation (PRC) for small renal masses under local anaesthesia and conscious sedation (LACS), to assess the safety and effectiveness of this approach, as PRC is typically performed under general anaesthesia (GA). Patients and methods: We retrospectively reviewed PRC under LACS from 2003 to 2017. We analysed perioperative parameters between patients who successfully underwent PRC under LACS and patients with post-procedural complications or treatment failure (renal mass enhancement after successful intraoperative tumour ablation). Two-sided non-parametric and Fisher's exact tests were performed to compare uncomplicated or disease-free PRC with the complication or treatment failure group, respectively. Results: A total of 100 PRCs under LACS were performed during the study period. Of these patients, six patients had at least one postoperative complication (6%), and treatment failure was diagnosed in nine patients (9%) after PRC [mean (SD) follow-up of 42.7 (26.6) months]. The procedural failure rate was 1%. No ablations were converted to GA. The mean tumour size was smaller in patients who had no complications during PRC compared to those who did, at a mean (SD) of 2.2 (0.6) cm vs 3.0 (1.0) cm ( P = 0.039). The use of more intraoperative probes during the PRC was also associated with complications, at a mean (SD) 3.0 (1.4) vs 1.8 (0.8) ( P = 0.021). Conclusions: PRC under LACS is an effective and safe procedural approach for managing small renal masses with low complication, treatment failure, and procedural failure rates. Larger renal masses and intraoperative use of multiple probes is associated with an increased risk of PRC complications. Abbreviations: BMI: body mass index; CCI: Charlson Comorbidity Index; GA: general anaesthesia; LACS: local anaesthesia and conscious sedation; PRC: percutaneous renal cryoablation; R.E.N.A.L.: Radius, Exophytic/Endophytic, Nearness, Anterior/Posterior, Location